Prevalence of Salmonella spp. in chicken and beef from retail outlets in Malaysia - Abu Bakar, Shafini; Radu, Son; Mahyudin, Nor Ainy; Rukayadi, Yaya; Tuan Chilek, Tuan Zainazor (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
The prevalence of Salmonella in chicken and beef sold in retails outlets in Malaysia was determined by analysing 312 raw beef and chicken meat samples including their processed products. Samples purchased from supermarkets, butcher shops and wet market, which being classified into raw, minced and processed chicken and beef. A total of 86 (27.6%) samples were found positive for Salmonella spp., with chicken meat samples (40.4%) showed greater presence compared to beef (15.4%). Highest presence of Salmonella were detected from wet market samples (35.4%), followed by supermarket (26.9%) and butcher shop (21.3%). The prevalence of Salmonella were higher in unpacked chicken meat (84.8%), followed by unpacked beef (27.8%). Salmonella serovars were identified as S. Enteritidis, S. Hadar, S. Dublin, S. Anatum, S. Stanley, S. Gallinarum, S. Choleraesuis and S. Typhimurium. Detection of 8 Salmonella serovars showed possibilities of cross contamination in various sources either at slaughtering house, processing plant or until storage at retails level. Improper cooking method on meats and hygiene practices prior to consume should be avoided in order to ensure food safety before ingestion.